2014
DOI: 10.5812/archneurosci.19257
|View full text |Cite
|
Sign up to set email alerts
|

Separating Mental Disorders Using Vestibular Field Potentials

Abstract: Background: Absence of quantitative techniques for objectively diagnosing many brain changes associated with mental illnesses hampers early intervention and effective treatment. Known bidirectional neural pathways closely link the vestibular system and regions involved in emotion processing. Objectives: To assess whether Electrovestibulography (EVestG) can detect specific neural responses, using an ear probe and tilt chair, to provide a quantitative indirect measure assessment of brain regions and pathways fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Both are equally valid explanations of the results. EVestG depression studies 51,52 showed no large variation in AP width (the key EVestG feature herein). This suggests the improvement may be in both depression and mTBI symptomatology.…”
Section: Discussionmentioning
confidence: 66%
“…Both are equally valid explanations of the results. EVestG depression studies 51,52 showed no large variation in AP width (the key EVestG feature herein). This suggests the improvement may be in both depression and mTBI symptomatology.…”
Section: Discussionmentioning
confidence: 66%
“…Otolith dysfunction was more pronounced in mTBI participants with anxiety, depression, and post-traumatic stress. The authors hypothesized this to be due to a multisensory mismatch and highlighted shared neural pathways between the vestibular system and emotion processing (Maller et al, 2014). The significance of this and causal relationship requires further study.…”
Section: Vor and Mtbimentioning
confidence: 99%